Mediators, confounders and effectiveness of interventions for medication adherence after stroke. (1st October 2020) - Hill, James; Harrison, Joanna; Raj, Sonia; Gregary, Bindu; Timoroksa, Anne-Marie; Gibson, Josephine
Abstract: After a stroke, people are left with an increased risk of recurrence. One of the primary methods of prevention is the use of a range of medications, but adherence to these is often low. This article evaluates and summarises three systematic reviews that investigate possible underlying reasons for this and how to overcome these barriers.